Oral health during pregnancy: an analysis of interprofessional guideline awareness and practice behaviors among prenatal and oral health providers - Cheryl A. Vamos; Morgan Richardson Cayama; Helen Mahony; Stacey B. Griner; Rocio B. Quinonez; Kim Boggess; Jason Beckstead; Ellen M. Daley (BMC, 2023)
Abstract Background Poor oral health during pregnancy has significant implications across the life course, including increased risk for adverse pregnancy, birth outcomes, and the development of early childhood caries. In efforts to improve perinatal oral health in the United States, a set of national interprofessional guidelines were developed that include recommended practice behaviors for both oral health providers and prenatal providers. The purpose of this study was to examine guideline awareness, familiarity, beliefs, and practice behaviors among both provider types. Methods Prenatal providers and oral health providers in Florida were recruited via random and convenience sampling to complete an online survey guided by the Consolidated Framework for Implementation Research (CFIR) and the Cabana Framework. The present analysis focused on the Individuals Involved domain (CFIR), awareness and familiarity with the guidelines (Cabana Framework), confidence, and practice behaviors as recommended by prenatal oral health guidelines (assess, advise, refer, share/coordinate). Data were analyzed using chi-square tests, independent samples t-tests, Pearson correlation coefficients, and one-way analysis of variance (ANOVA) and analyses were conducted in SPSS. Results Prenatal and oral health providers did not differ significantly in their awareness of the guidelines, but awareness was significantly associated with three of the four practice behaviors for prenatal providers. Familiarity with the guidelines was significantly higher among oral health providers and was associated with all four practice behaviors for both provider types. Five out of ten oral health belief items were significantly associated with practicing the guidelines among prenatal providers, but only two among oral health providers. Confidence in performing the practice behaviors was significantly associated with guideline implementation among both groups. Years in practice was significantly associated with performing practice behaviors for prenatal providers, but not for oral health providers. Conclusions Our findings highlight the importance of professional organizations and the role of clinical guidelines on practice behaviors. Although provider education is a key implementation strategy, organizational and policy-level system changes could also be critical in supporting practice behaviors.